Aristóteles: fronteiras da política - Leandro, Giácomo Fioritti (2024)
In the Nicomachean Ethics, by emphasising the opposition between science, which is universal and necessary, and the field of action, which is particular and contingent, Aristotle presents the concept of φρόνησις, previously associated with theoretical philosophy, as an eminently practical virtue, more related to deliberation and to the figure of the politician. In the 20th century, it divided the interpretation of his practical philosophy into more intellectual and more empirical interpretations. On the one hand, it was thought that the moral agent would continue to rely above all on the knowledge of universal laws and principles of action, like Plato, and that it was simply up to the φρόνιμος to apply them to particulars, i.e. to realise this articulation, but without ceasing to understand, as a sage, the human ends. On the other hand, however, it has been argued that, now that a real "gap" has been created between the universal and the particular, the good agent, rather a prudent one, could only orient himself in the particular itself, and thus more properly know the most appropriate means for each circumstance in which he must act. Now, starting from the association between φρόνησις and politics, what we have pointed out is that Aristotle's reformulation raises not only the problem of the status of φρόνησις, but also the problem of the status of politics itself. Should politics, which finds its main exponent in the figure of the φρόνιμος, the prudent man or the man of practical wisdom, be concerned only with the choice of means or even with the ends of man? By pointing out the distance between theory and practice, did Aristotle really bring human affairs back to collective debates and back to the assembly deliberations? Or are there other boundaries to political knowledge?